SOME CYCLIC FIXED POINT RESULTS FOR CONTRACTIVE MAPPINGS - Radenović, Stojan; Chandok, Sumit; Shatanawi, Wasfi (Bulletin of Natural Sciences Research, 2016)
In this paper, we obtained some new cyclic type fixed point theorems using C-class functions in the framework of metric spaces. Our results extend, generalize, improve and enrich some recent results in the existing literature.